A dual-camera single-shot lifetime method with fully controllable exposure gates for pressure-sensitive paint measurements on fast-rotating surfaces. (1st October 2022) - Li, Yongzeng; Dong, Zhe; Peng, Di; Liu, Yingzheng
Abstract: This paper proposes a dual-camera single-shot lifetime method for pressure-sensitive paint (PSP) measurements on fast-rotating surfaces. Two cameras with fully controllable exposure gates are used for image acquisition to reduce the motion blur due to the open-ended exposure of the interline transfer charge-coupled device camera which was typically used for the single-shot lifetime method. The images can thus be processed without deblurring for a wider rotating speed range than is possible with existing techniques. More importantly, both frames have equal exposure times and therefore equal blur lengths. This enables precise pixel-to-pixel image matching and minimizes image registration errors. In addition, the signal strengths of the frames can be balanced, enabling shot-noise-induced errors to be reduced by independent adjustment of the aperture ratio. A pressure uncertainty estimation model is established to evaluate the measurement errors, which helps determine the system parameters. The dual-camera PSP system is calibrated and then validated through the surface pressure measurement of a fast-rotating disk. It is found that the exposure time t e has little effect on the PSP sensitivity, whereas the delay time t d affects both the pressure sensitivity and the measurement error. Both t e and t d are set to 5 μs in the rotating disk experiment. Images with a blur length of 1.4 pixels are captured and processed without deblurring to yield reasonable surface pressure results. The pressure error is decreased from 1.05 to 0.65 kPa by increasing the aperture ratio F from 2 to 4.